Parenting Patterns and Child Behavior: A Comparative Study of Single and Full Parents - Maulida, Ihda; Abdurrahman, Abdurrahman (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2024)
This study aims to compare the parenting patterns of single and full parents and their impact on child behavior in Sementara, Pantai Cermin Sub-district, Serdang Bedagai Regency, Indonesia. Parenting plays a crucial role in shaping a child's personality and future. Based on Bronfenbrenner's ecological theory, the home environment, especially parental parenting, has the greatest influence on child development. This study focuses on three parenting styles: authoritarian, democratic, and permissive. Authoritarian parenting is characterized by strict rules and limited freedom, while democratic parenting prioritizes the child's interests and involves discussions between parents and children. Permissive parenting provides loose supervision and unrestricted freedom for children to behave and act as they wish. Previous studies have shown that single mothers tend to apply authoritarian parenting, resulting in spoiled children with difficulty interacting, while single fathers tend to apply permissive parenting, leading to more independent children who are easier to make friends. Additionally, authoritarian, democratic, and permissive parenting styles have been associated with aggressive behavior in children, obtained through social learning. Democratic parenting has been found to increase children's motivation and achievement at school, while authoritarian parenting inhibits children's socialization skills. This study provides important insights into the impact of parenting patterns on child behavior in the context of single and full parents in Sementara, Indonesia.